Isolated C3 hypocomplementemia as an early predictor of chronic kidney disease in lupus nephritis - Andrulli, Simeone; Manenti, Lucio; Reggiani, Francesco; Pisani, Isabella; Giannese, Domenico; Vischini, Gisella; Valsecchi, Giovanni; Godeas, Giulia; Gigliotti, Giuseppe; Esposito, Pasquale; De Giovanni, Paola; Murtas, Corrado; et al. (Frontiers in Immunology, 2025)
ObjectiveThe role of complement in the long-term renal survival of patients with lupus nephritis (LN) remains poorly understood. Recent studies suggest its potential impact; however, long-term data are lacking.MethodsThis multicenter, observational, retrospective study aimed at investigating the influence of complement levels on long-term renal outcomes in LN patients. We evaluated whether isolated C3 hypocomplementemia (i-LowC3), defined as serum low C3 (≤80 mg/dL) and normal C4 (>10 mg/dL) six months after kidney biopsy is associated with subsequent risk of chronic kidney disease (CKD), End Stage Kidney Disease (ESKD) or death.Results445 patients with LN were studied (median follow-up 4.9 years). Based on six-month C3/C4 levels, patients were categorized into i-LowC3 (91 patients) and controls (354 patients). Over the first six months, serum C3 and C4 levels increased by a median of 20 mg/dL and 5 mg/dL, respectively. i-LowC3 was significantly associated with twice the risk of a poor outcome, including CKD, ESKD, composite outcome of CKD or death and ESKD or death, with lower survival rates for all these outcomes compared to controls (P < 0.001). Multivariate Cox regression analysis revealed a lower risk of CKD and CKD or death with increases in C3 levels during the first six months, while i-LowC3 was associated with an independent higher risk for these outcomes.ConclusionThe trajectory of serum C3 levels within the first six months appears to predict long-term renal prognosis of LN patients. These findings support the use of i-LowC3 as a low-cost, readily available biomarker to guide early treatment of LN patients.